AXIOLOGY OF NEOLOGISMS WITH A COLORATIVE COMPONENT (Based on the Material of Online-Dictionaries) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-1-79-90Abstract. The purpose of the article is to identify lexical and semantic features of color designation in determining the national cultural specificity of language and speech means. This article illustrates the key characteristics that clearly reflect semantic shifts in vocabulary caused by rethinking axiological components: the frequent use of the green lexeme as part of neologisms; the creation of a new system of values with the help of neologisms with a positive connotation; the emergence of terms naming a person by the professional activity; a significant increase in the group of neologisms associated with economic and environmental discourses; the use of words related to gastronomic culture; interest in the problems of the impact of modern technologies on human life. The study of neologisms as a means of representing values and forming an assessment expands the range of research in the field of axiology and neology.Key words: axiology, color component, neologism, value, environmental friendliness